INTERNALISASI NILAI DISIPLIN DALAM PEMBELAJARAN PKN PADA SISWA DI SMP NEGERI 7 PELAIHARI - Sapriadi Sapriadi (JURNAL SOCIUS, 2014)
Internalization of discipline value into civics lessons at SMP Negeri 7 Pelaihari has not been maximally implemented. This research used qualitative method. The results of research indicate that: 1) In internalizing the value of discipline for students a program that is integrated in the learning of Civics is needed. 2) In the effort of developing  students’ discipline, a strategy that can embed value of  strong discipline.3) In implementing the value of discipline, the awareness of the value of discipline and good cooperation among the entire members of school community. 4) The violations of school rules still frequently happen; this may be caused by students themselves or teachers or other education personnel who are unable to provide good examples and proper role models for students. For all members of school community it is suggested to work together in the effort of instilling the value of discipline for students.Keywords: Internalization, Value Discipline, Student, Civics.